EMPOWERMENT OF THE ACEH COMMUNITY IN KUALA LUMPUR MALAYSIA FOR CAPACITY AND PREPARATION FOR INDEPENDENCE - Jullimursyida; Mohd. Heikal; Herman Fithra; Teuku Zulkarnaen; Darmawati; Rico Nur Ilham; Ahmad Fauzul Hakim Hasibuan (RADJA PUBLIKA, 2023)
Unimal International Community Service Activities (PKM), this PKM aims to provide support to the Acehnese community of Indonesian Migrant Workers (PMI). This collaboration involves the Embassy of the Republic of Indonesia (KBRI) in Kuala Lumpur. The main mission of the Indonesian Embassy's PKM is to provide training and outreach to PMI who face various problems, so that they can avoid illegal practices or abuse of labor. PMI are provided with training appropriate to their professional field, as well as additional understanding and skills to develop their potential and soft skills, so that they can compete and become professional workers abroad. Implementation of the PKM program includes several stages, starting from surveys/explorations, fundraising, technical meetings, holding international PKM seminars, to reporting. From the results of this activity, it can be seen that PMI who took part in the program were able to understand the material presented and receive the information well. Positive responses from PMI were seen throughout the activity, where they felt entertained and could fill their time while waiting for their problems to be resolved. The main target of this activity is to increase PMI competency and independence, as well as improve their soft skills so that in the future, when they no longer work as PMI, they will still have an advantage in the international job market. In this way, PMI's personal protection can be more guaranteed.